Stability Analysis of Accumulative Formation Slope Reinforced by Inclined Micropile Group - WANG Xiaozhe; LIU Linlin (Renmin Zhujiang)
Based on the finite difference software FLAC3D and strength reduction method, this paperanalyzes the law between the inclination angle of pile and the supporting effect of accumulativeformation slope reinforced by the inclined micropile group. The inclination angle of pile is theangle between the micropile group and the vertical plane. If inclination to the top of the slope,the angle is negative, otherwise it is positive. The simulation results of slopes with aninclination of 30° show that:①When the inclination angle of the pile changes from -30° to 0°,the supporting effect increases first and then decreases, with best supporting effect ininclination of-20°; ②When the inclination angle of the pile is between 10° and 30°, itssupporting effect has no obvious advantage over the vertical micro pile; ③When the inclinationangle of pile changes from 40° to 60°, the supporting effect increases continuously. Comparedwith the vertical micropile group, the supporting effect is significantly improved, with bestsupporting effect in inclination of 60°; ④The angle between the micropile group and thediscontinuous surface is defined as φ. When φ> 90°, the inclined micropile group has asignificantly better supporting effect than the vertical micropile group; ⑤Inclined micropilegroup do not change the depth of the potential sliding surface of the accumulative formation slope,but affects its distribution along the slip zone; ⑥Uniform load is applied to the top of the slope, and the peak bending moment and peak shear force of each row of piles appear at thediscontinuous surface, and the relationship is basically as follows: back row piles> middle rowpiles> front row piles; ⑦In the optimal support scheme, the inclined micropile group cooperateswith the soil in front of the pile to form a “combined foundation” to jointly bear the thrust ofthe soil and landslide behind the pile, and the supporting effect is significantly improvedcompared with the vertical micropile group, the body stress is significantly reduced.